IMPLEMENTASI PERMAINAN TRADISIONAL GOBAK SODOR TERHADAP MOTIVASI BELAJAR SISWA DALAM MATA PELAJARAN PKN DI SEKOLAH DASAR - Lula Dwi Kemaliah; Nina Kania Dwi; Santika Az Zahra; Rana Gustian Nugraha (PRIMARY EDUCATION JOURNAL (PEJ), 2023)
This article examines the implementation of the traditional game "Gerobak Sodor" in increasing students' learning creativity in Citizenship Education (PKN) subjects in elementary schools. Gerobak Sodor is a game that involves traditional and local elements which can be an effective tool for improving the PKN learning process. This research uses a questionnaire as a tool to collect data from students involved in the game. The results of this research indicate that the Sodor Cart game can be an effective tool in increasing learning motivation and understanding of PKN concepts, especially in the context of cooperation and mutual cooperation.